Transport and Conductance in Fibonacci Graphene Superlattices with Electric and Magnetic Potentials - 尹贻恒 牛燕雄 丁铭 刘海月 梁振江 (Chinese physics letters, 2016)
We investigate the electron transport and conductance properties in Fibonacci quasi-periodic graphene superlat- rices with electrostatic barriers and magnetic vector potentials. It is found that a new Dirac point appears in the band structure of graphene superlattice and the position of the Dirac point is exactly located at the energy corresponding to the zero-averaged w~ve number. The magnetic and eleetr/c potentials modify the energy band structure and transmission spectrum in entirely diverse ways. In addition, the angular-dependent transmission is blocked by the potential barriers at certain incident angles due to the appearance of the evanescent states. The effects of lattice constants and different potentials on angular-averaged conductance are also discussed.